2010
DOI: 10.1111/j.1469-7580.2010.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative morphometry of the orbit in Chinese adults based on a three‐dimensional reconstruction method

Abstract: The three-dimensional (3D) reconstruction technique serves as a practical tool in diagnosis, surgical planning, and outcome prediction of plastic and reconstructive surgery. In our study, the morphologic features of the Chinese adult orbit were described by 11 anatomic parameters using a 3D reconstruction technique. Sixty-four Chinese adults were selected randomly from patients who had undergone craniofacial computed tomography (CT) scans to diagnose conditions other than craniofacial or orbital deformations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
65
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 14 publications
13
65
1
5
Order By: Relevance
“…This could be due to racial differences and also they have not compared the floor length between the genders irrespective of side. Yongrong ji et al [7] and Bryan C. Mendelson et al [8] have reported in their CT scan studies that the floor length of orbits in males is significantly larger than in females, which correlates with the present study. Yongrong ji et al [7] (CT scan) Both the previous studies have reported that there was no significant difference in the floor length between the two sides.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This could be due to racial differences and also they have not compared the floor length between the genders irrespective of side. Yongrong ji et al [7] and Bryan C. Mendelson et al [8] have reported in their CT scan studies that the floor length of orbits in males is significantly larger than in females, which correlates with the present study. Yongrong ji et al [7] (CT scan) Both the previous studies have reported that there was no significant difference in the floor length between the two sides.…”
Section: Resultssupporting
confidence: 81%
“…The reasons of lower values of the roof length compared to the results of the present study could be because of racial differences as their study population is different and also relatively smaller sample size (n= 50) in their study. Yongrong ji et al [7] and Bryan C. Mendelson et al [8] studied the orbital parameters in CT scans. The results of their study are similar to that of the present study which shows that the roof length is larger in males when compared to females.…”
Section: Resultsmentioning
confidence: 99%
“…This point is a surgical landmark, but is difficult to locate in CT images [6,10,14,17,23]. The starting point in this study is analogous to the point proposed by Ji et al [12] -it is an external bony point in the intersection between the horizontal line that divides the orbit in two equal parts (upper and lower) and the lateral bony margin. This point is equivalent to the Whitnall's tubercle -approximately 1 cm inferior to the frontozygomatic suture and approximately 4-5 mm behind the lateral orbital rim, where attached are the lateral canthal tendon, the lateral rectus check ligament, lateral horn of the levator aponeurosis, suspensory ligament of the lower lid (Lockwood's ligament), the lacrimal gland fascia and the orbital septum [5,16].…”
Section: Discussionmentioning
confidence: 99%
“…The starting point for measurements in the medial wall was, in this study, the verge of the posterior lacrimal crest, and the final point was the medial optic canal border. Similar final points, to which the distance from the starting point was measured, were provided by Ji et al [12], who used the frontomaxillary suture as the starting point (easy to find on a dry skull and intraoperatively, but difficult to establish in CT imaging). Other authors provided as a measurement point (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation